The New Great Game : Bolood and Oil in Central Asia - Kleveman, Lutz (Rawalpindi Army Publishing House, 2012)
"In The New Great Game, Lutz Kleveman gives us a fearless, insightful, and exacting portrait of a new battleground in the violent politics and passion of oil: Central Asia, known as the "black hole of the earth" for much of the last century. The Caspian Sea contains the world's largest amount of untapped oil and gas resources. It is estimated that there might be as much as 100 billion barrels of crude oil in the former Soviet republics of Kazakhstan and Azerbaijan alone." "Using the concept of the "Great Game" that Rudyard Kipling immortalized in his novel Kim, Kleveman argues that now a New Great Game rages in the region, a modern variant of the nineteenth-century clash of imperial ambitions of Great Britain and Tsarist Russia. Only this time the stakes are raised. Desperate to wean itself from dependence on the powerful OPEC cartel, the United States is now pitted in this struggle against Russia, China, and Iran, all competing for dominance of the Caspian region, its resources and pipeline routes." "Complicating the playing field are transnational energy corporations with their own agendas and the brash new, Wild West-style entrepreneurs who have taken control after the collapse of the Soviet Union. Traveling thousands of miles, from the Caucasus peaks across the central Asian plains down to the Afghan Hindu Kush, Kleveman met with the principal Great Game actors between Kabul and Moscow: oil barons, generals, diplomats, and warlords."--Jacket.
Includes Map, Note, Bibliography and Index.
Keywords: Petroleum Industry and Trade--Political Aspects -- Caspian Sea Region -- Geopolitics -- Asia, Central